Treatment-free remission in patients with chronic myeloid leukemia: literature review - A. N. Petrova; E. Yu. Chelysheva; A. G. Turkina (Онкогематология)
Tyrosine kinase inhibitors have radically changed the course of chronic myeloid leukemia, significantly increasing survival and reducing the risk of disease progression. Nearly 50–70 % of patients achieve a consistently low or undetectable level of minimal residual disease – a deep molecular response. The long-term tyrosine kinase inhibitors treatment in about one-third of patients is accompanied by toxicity which impairs the quality of life. Therefore, the safe treatment discontinuation is relevant. The results of clinical trials have shown 40-60% possibility of maintaining treatment-free remission in patients with long-term deep molecular respons; however, all patients with molecular relapse regain molecular remission after the resumption of tyrosine kinase inhibitors therapy. Currently, clinical and biological factors associated with maintaining treatment-free remission are being studied. It is assumed that cessation of tyrosine kinase inhibitors therapy can improve the quality of life, but approximately 30 % of patients are reporting musculoskeletal pain – so called “withdrawal syndrome” – that begins or worsens after stopping tyrosine kinase inhibitors therapy. The mechanisms for the development of this phenomenon are currently unclear. Thus, many aspects concerning treatment-free remission require to be studied, which determines the importance of clinical trials in this area.